Rethinking Phenotypic Categorization: Evidence From Morphological and Life‐History Traits in Spiny Lizards (Sceloporus) - Isaac Emmanuell Diaz‐Ortega; José Jaime Zúñiga‐Vega; Oscar Flores‐Villela; Hibraim Adán Pérez‐Mendoza (Ecology and Evolution)
ABSTRACT The evolution of phenotype has historically been studied by classifying traits into categories, as traits within each category often exhibit close associations. However, these categories are not independent of one another. Thus, the phenotype may function as an integrated set of traits rather than as isolated units. In this study, we employed various phylogenetic comparative methods to explore evolutionary correlations among traits, estimate and compare phylogenetic signals, and evaluate evolutionary models to assess the validity of the historical categorization of phenotypic traits in spiny lizards of the genus Sceloporus. We categorized these traits as either morphological or life‐history traits, including eight morphological traits and seven life‐history traits, such as trunk length, head width, snout‐vent length, clutch size, hatchling length, and size at maturity. Our analyses revealed covariation in the evolution of traits both within and across categories. Differences in phylogenetic signals between categories were also observed, though these results should be interpreted with caution. Additionally, the evolutionary models varied between categories. Our findings suggest that estimates of phylogenetic signals and covariation between morphological and life‐history traits are independent of historically assigned categories. Therefore, this supports the notion that traits should be compared and analyzed in an integrated manner, regardless of their category. We discuss how evolutionary mechanisms, such as fecundity selection, may influence traits across different categories (e.g., trunk length, hatchling length, and clutch size), challenging the appropriateness of traditional phenotypic categorization in evolutionary studies of Sceloporus.